Pathological and Problem Gambling among Veterans in Clinical Care: Prevalence, Demography, and Clinical Correlates. (25th April 2013) - Westermeyer, Joe; Canive, Jose; Thuras, Paul; Oakes, Michael; Spring, Marline
Abstract : Background and Objectives: The aim of the study was to estimate prevalence rates of pathological gambling and problem gambling among veterans receiving VA care, since several studies have suggested that VA patients may be at increased risk to these conditions. Sample: consisted of 1, 999 veterans randomly selected from VA centers and community clinics in the Albuquerque and Minneapolis catchment areas. Women and younger veterans were oversampled, due to anticipated low rates in these two groups. Results: revealed that the lifetime prevalence rate of pathological gambling weighted for current VA patients was 2.0%, twice the general adult population rate. Current 1‐year weighted prevalence of pathological gambling was .9%, with an additional .2% having continued problem gambling and .9% recovered. Lifetime weighted problem gambling rate was 8.8%. Altogether, 10.7% had lifetime pathological gambling or problem gambling. Women had higher rates of pathological gambling, but similar rates of problem gambling compared to men. The greater prevalence of pathological gambling for younger veterans aged 20–29 (1.3%) compared to veterans aged 30–39 (.8%) was unusual and warrants further investigation. Conclusions and Scientific Significance: Veterans in VA care have higher rates of gambling problems than the general adult population. Female and young veterans have rates higher than those observed in other surveys of women and young adults. (Am J Addict 2013; 22:218–225)